Uji Beberapa Konsentrasi Ekstrak Biji Pinang (areca catechu l.) Untuk Mengendalikan Kepik Hijau(Nezara viridula l.) (Hemiptera: pentatomidae) di Laboratorium - Fitriani, Melli; Laoh, J. Hennie; Rustam, Rusli (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Green stink bug (Nezara viridula L.) is an important pest in soybean. The use of synthetic chemical control has many negative impacts such as the occurrence of pest resistance, pest resurgence and environmental pollution. Botanical pesticides such as betel nut (Areca catechu L.) is one alternative pest control to reduce the use of synthetic chemical pesticides. The purpose of this study is to obtain appropriate concentrations of betel nut extracts to control green stink bug (N. viridula L.) in soybean crops. This research was conducted in the pest laboratory of the Faculty of Agriculture, University of Riau by using a completely randomized design with 5 treatments and 4 replications. Betel nut extract treatments given was 0 g/l of water, 10 g/l of water, 20 g/l of water, 30 g/l of water, 40 g/l and 50 g/l of water. Concentration of 50 g/l of water caused total mortality 97.5 %. Appropriate concentration to kill 95 % of test insects is 4.64 % equivalent to 46.4 g/l approaches 50 g/l of water. Keyword: Soybean (Glycine max L.), Green stink bug (Nezara viridula L.), Betel nut (Areca catechu L.)